THE INTEGRATION OF FOLKLORE ASLOCAL WISDOM IN TEACHING NARRATIVE TEXT: A CASE STUDY AT SMA MUHAMMADIYAH BERAU - Sutiawati Sutiawati; Surono Surono; Dwi Santoso (PROJECT (Professional Journal of English Education), 2023)
Integrating local wisdom as a medium for narrative reading makes it easier for teachers to create interesting learning experiences. The objective of this study was to investigate the teacher's strategy in teaching narrative texts by integrating folklore as local wisdom, analyze the student's narrative text produced by students when teaching strategies were implemented, and find out students' responses to teachers' strategy in narrative learning using folklor as local Wisdom. The researchers conducted qualitative research using case study designs. Two English teachers and 30 students from Muhammadiyah Berau High School, East Kalimantan, participated in the study. Data was collected using semi-structured interviews, class observations, and documentation.The findings reveal that teachers use sensory strategies, figurative language, and living words to teach narrative texts through three processes: pre-teaching, while-teach, and post-teacher. Increases enthusiasm and motivation among students. The rating shows a significant increase in the average score, from 85 to 87. Students also tell narrative texts and find folklore as an interesting medium to learn, as it enhances critical thinking and makes imagination flourish.